Prognostic significance of MicroRNA-34 expression in patients with gastric cancer: evidence from a Meta-analysis - Chao-Fan Gong (临床与病理杂志, 2026)
Objective: MiR-34 is a prospective prognostic marker in cancer, but its association with GC is still controversial. To assess the clinicopathological and predictive significance of miR-34 expression in GC we performed this meta-analysis. Methods: Data were extracted from eligible studies.Meta-analysis was performed with STATA12.0software. Results: A total of 7 papers (806 cases) were included. A meta-analysis of clinicopathological variables revealed a correlation between miR-34 expression and differentiation grade (OR =0.95, 95% CI, 0.74~1.22, P<0.05). However, no significant associations were found in other variables. Subgroup analysis by stratified detection methods showed no significative associations between the expression of miR- 34 and clinicopathological variables in GC. The correlation between miR-34 expression and poor prognosis was statistically significant (HR =1.52, 95% CI, 1.14~1.90, P<0.05). Conclusion: This study shows that miR-34 is a potential prognostic marker of GC.Future research with larger amount of samples should be developed to investigate thoroughly the role of miR-34 expression in GC.